Harnessing local wisdom to conserve biodiversity on the southern coast of Gunung Kidul, Indonesia (Asian Journal of Ethnobiology, 2024)
Abstract. Syamsi RN, Rosyida SH, Allysa TN, Hanifah W, Dianti, Sunarto, Nazar IA, Md. Naim D, Setyawan AD. 2024. Harnessing local wisdom to conserve biodiversity on the southern coast of Gunung Kidul, Indonesia. Asian J Ethnobiol 8: 115-121. Coastal biodiversity is a crucial component of ecosystems. However, it faces significant threats due to land use changes driven by increasing societal needs. Coastal areas are increasingly shrinking due to changes in land use and exploitation of areas such as the misuse of coastal land for fish ponds which should be designated as conservation areas. This situation impacts the sustainability of local communities and the management of resources, highlighting the role of communities in empowering local wisdom. This study aimed to understand the local wisdom of the coastal community in Kanigoro Village, Saptosari Sub-district, Gunung Kidul District, Yogyakarta Province, Indonesia in managing natural resources and conserving coastal biodiversity. The research used qualitative observational methods, including direct interviews with respondents. Data were collected through direct interviews with a total of 74 respondents, aged between 37-55 years, including five key respondents, and through Focus Group Discussions (FGD) on topics such as local wisdom, technological innovation, community participation, threats or challenges, and conservation strategies to understand the community’s views on local biodiversity conservation. The results of this study revealed the presence of 17 protected species from 17 families. They identified three traditional customs still preserved today: labuhan/larungan, musim gugur gunung, and rasulan. The community continues to apply conservation principles rooted in local wisdom in their daily activities, such as prohibiting of catching and utilizing protected species, and forbidding the collection or harvesting of sand and coral to preserve these resources. The community plays an active role in preserving the biodiversity of wildlife and the surrounding environment. Local wisdom has the potential to sustain and strengthen ecosystem integrity, while improving the well-being of local communities by maintaining the availability of coastal biodiversity.
Keywords: Coastal biodiversity, coastal communities, conservation, local wisdom